Drivers of Sharia P2P Lending Adoption in Indonesia: An AISAS Model Approach - Ismail, Juniaty; Supri, Zikra; Dukalang, Hendra; Budianto, Rahman; Katili, Chitra Yuliashri (Faculty of Islamic Economics and Business, Universitas Islam Negeri Ar-Raniry, 2024)
The challenge of accessing capital for Micro, Small, and Medium Enterprises (MSMEs), compounded by low financial literacy, has led to limited awareness among MSME actors regarding sharia-based Peer-to-Peer (P2P) Lending. This study investigates the response of MSME actors on Sulawesi Island, Indonesia, to the adoption of fintech-based sharia P2P lending services using the AISAS (Attention, Interest, Search, Action, and Share) model. Distinct from previous research, this study specifically focuses on the utilization of sharia-based P2P fintech by MSMEs in Sulawesi, applying the AISAS model approach. A quantitative approach was employed, gathering data from 580 MSME respondents in Sulawesi, and analyzed using Smart-PLS 3.2.9 software. The results indicate that interest, search, and sharing behavior are significant predictors of sharia-compliant P2P lending adoption, while attention and action demonstrate no significant influence. This study offers valuable insights for sharia fintech P2P lending service providers and government bodies supporting MSMEs, particularly in Sulawesi, stressing the importance of enhancing outreach to promote sharia fintech P2P lending as a more accessible and efficient capital source.========================================================================================================ABSTRAK – Pendorong Adopsi P2P Lending Syariah di Indonesia: Pendekatan Model AISAS. Akses permodalan masih menjadi tantangan signifikan bagi Usaha Mikro, Kecil, dan Menengah (UMKM) di Indonesia. Hal ini dipicu oleh rendahnya literasi keuangan para pelaku usaha yang berakibat pada rendahnya kesadaran akan produk keuangan syariah seperti layanan Peer-to-Peer (P2P) Lending. Penelitian ini mengkaji adopsi layanan P2P Lending Syariah di kalangan UMKM di Pulau Sulawesi, Indonesia, dengan menggunakan model Attention, Interest, Search, Action, and Share (AISAS). Berbeda dengan penelitian sebelumnya, studi ini berfokus pada pemanfaatan fintech P2P berbasis syariah oleh pelaku UMKM di Pulau Sulawesi. Menggunakan pendekatan kuantitatif, penelitian ini mengumpulkan data dari 580 pelaku UMKM dan dianalisis menggunakan Smart-PLS 3.2.9. Hasil penelitian menunjukkan bahwa minat, pencarian, dan berbagi berpengaruh signifikan terhadap adopsi P2P Lending syariah, sementara perhatian dan tindakan menunjukkan hal sebaliknya. Hasil penelitian ini berkontribusi kepada penyedia layanan P2P dan instansi pemerintah dalam mendukung pertumbuhan UMKM, khususnya di Sulawesi. Temuan ini menyoroti perlunya sosialisasi yang terarah untuk mempromosikan P2P Lending syariah sebagai solusi pembiayaan yang mudah diakses dan efisien.